Ultrasonography of the ulnar nerve loop in relation to the flexor carpi ulnaris tendon - Becciolini Marco; Pivec Christopher; Riegler Georg (Journal of Ultrasonography)
The purpose of this study is to present the ultrasound appearance of a previously undescribed-at-imaging variant of the ulnar nerve near the Guyon’s canal.